Korelasi Daya Dukung Tanah dengan Kuat Geser Menggunakan Alat Vane Shear dan Direct Shear - Adama, Riri Arinda; Setyanto, setyanto; Adha, Idharmahadi (Universitas Lampung, 2017)
The soft clay soil has expansive behavior that expands when exposed to water, this will be very dangerous to the construction to be built on it, because clay soil generally has a low shear strength and high compressibility. To know the parameters and characteristics of strong clay soil shear in an area, can use vane shear test and direct shear test. The soil samples were taken from Jabung, East Lampung for testing laboratory modeling on glass box with vane shear and direct shear tools with a weight of ± 130,730 grOn the direct shear tests when soil conditions remolded at a depth of 30 cm shear strength values obtained at 0.0743 kg/cm2, on vane shear test obtained 0.38 kg/cm2 with soil bearing capacity of 0.6048 kg/cm2, at a depth of 50 cm obtained a shear strength value of 0.0779 kg/cm2, on vane shear test obtained 0.54 kg/cm2 with soil bearing capacity of 0.6738 kg/cm2. In saturated soil conditions a depth of 30 cm obtained a shear strength value in the direct shear test of 0.0553 kg/cm2, the vane shear test of 0.46 kg/cm2 with a bearing capacity of 0.4116 kg/cm2, a depth of 50 cm obtained shear strength value of 0.0743 kg/cm2, the vane shear testing with a 0.65 kg/cm2 earned bearing capacity of 0.6308 kg/cm2. From the test results direct shear test and vane shear test known that the shear strength in direct shear tests is smaller than the vane shear test. Keywords: Vane shear, direct shear, Clay soil shear strength, Soil bearing capacity.